Development of failure criterion and reliability model for plastic encapsulated microcircuits at elevated environment - Poon, Wai Kiong. (2008)
The strength of the interfaces between dissimilar materials that make up an electronic component has important consequence on its failure mechanism. The mechanical integrity of such devices is thus determined by a material property that characterizes the resistance of material interface to fracture. Failure mechanisms resulting from the delamination of material interfaces leads to cracking (cleavage or fatigue) interconnections. It can also offer a path for electromigration and corrosion. Common failure delamination sites are between the chip/encapsulant interface and substrate/encapsulant interface. Cracks kinking from corners and interfaces of such packages also pose a reliability problem. Chip corners acts as possible stress concentration areas for the initiation and propagation of cracks. These corner cracks may propagate through the interface between a chip and an encapsulant or kink into the encapsulant depending on their relative critical stress intensity factors. Failures of such nature result in reduced reliability and perfor-mances in the electronic packages. Therefore, the knowledge of interfacial strength and kink cracks are important to the design of these devices.